2017
DOI: 10.17796/1053-4628-41.4.275
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Casein Phosphopeptide-Amorf Calcium Phosphate and Acidulated Phosphate Fluoride Gel on Dental Erosion in Primary Teeth: An in Vitro Study

Abstract: Under the conditions of this study, artificial saliva, CPP-ACP and 1.23% APF treatments were able to reduce erosive enamel loss produced by carbonated soft drink in primary teeth. However, 1.23% APF gel showed the highest protective effect against erosive enamel loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Studies have been conducted on the efficacy of toothpastes and topical creams containing casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) with fluoride in preventing erosive tooth wear from acidic beverages or solutions [32] , [33] , [34] . A randomized controlled trial was conducted by Maden et al [32] to investigate the effect of acidulated phosphate F (APF) gel and CPP-ACP on the dental erosion in primary teeth. They found that artificial saliva, CPP-ACP, and 1.23% APF treatments reduced erosive enamel loss produced by carbonated drinks in primary teeth.…”
Section: Classification Of Pmfs In Dentistrymentioning
confidence: 99%
“…Studies have been conducted on the efficacy of toothpastes and topical creams containing casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) with fluoride in preventing erosive tooth wear from acidic beverages or solutions [32] , [33] , [34] . A randomized controlled trial was conducted by Maden et al [32] to investigate the effect of acidulated phosphate F (APF) gel and CPP-ACP on the dental erosion in primary teeth. They found that artificial saliva, CPP-ACP, and 1.23% APF treatments reduced erosive enamel loss produced by carbonated drinks in primary teeth.…”
Section: Classification Of Pmfs In Dentistrymentioning
confidence: 99%
“…All studies have shown favorable results. They have used fluoride, casein phosphopeptide-amorf calcium phosphate, and acidulated phosphate fluoride gel, 15 CPP-ACPF and nano-hydroxyapatite, 16 air-abrasion pre-treatment with bioactive glass 45S5, 17 and many other treatments. These research reports show the seriousness of the surface roughness problem associated with soft drinks.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that any demineralization on the enamel surface caused by the bleaching gel will be counteracted by the remineralizing effect of saliva within 24 hr (Basting et al, 2003; Sulieman, Addy, Macdonald, & Rees, 2004). Maden, Acar, Altun, & Polat (2017) compared improvements in surface roughness of eroded enamel surface among three groups treated with 1.23% APF gel or Tooth Mousse or immersed in artificial saliva (control group). They reported that although average surface roughness of eroded enamel surface decreased in all groups, the greatest reduction was found for the group exposed to 1.23% APF gel.…”
Section: Discussionmentioning
confidence: 99%